1977
DOI: 10.1021/ac50009a050
|View full text |Cite
|
Sign up to set email alerts
|

Techniques in gas chromatography/chemical ionization mass spectrometry

Abstract: A gas chromatograph has been directly coupled to a magnetic mass spectrometer without a separator. With different source configurations both low pressure (El) and high pressure (Cl) mass spectra can be obtained. The direct coupling causes little loss In chromatographic resolution. Operating parameters of the instrument are discussed and examples of GC/CIMS are given. Flows as high as 20 ml/min (He, STP) or 10 ml/min (N2, CH4, STP) have been taken into the mass spectrometer without degradation of performance. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The modifications for CI operation have been described previously. 30,31 The electron energy for the low voltage experiments was calibrated with the appearance energy of the [CH,]' ion in methane. *' Different conditions were used for different experiments, but the spectra for a given set of stereoisomers were obtained under conditions as nearly identical as possible for each type of experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The modifications for CI operation have been described previously. 30,31 The electron energy for the low voltage experiments was calibrated with the appearance energy of the [CH,]' ion in methane. *' Different conditions were used for different experiments, but the spectra for a given set of stereoisomers were obtained under conditions as nearly identical as possible for each type of experiment.…”
Section: Methodsmentioning
confidence: 99%
“…We wish to report the relatively simple operating and optimization procedures for obtaining in-beam/CI spectra which are comparable to spectra obtained by FD/CI. EXPERIMENTAL The experiments were performed with a duPont 21-llOB mass spectrometer which has been modified for high pressure operation (11). In addition, a data acquisition system has been added to the instrument to allow rapid scanning (4.5 s for the mass range of 28 to 600) of spectra, every 6.5 s.…”
Section: Literature Citedmentioning
confidence: 99%
“…Few investigations of this kind have been reported. Experiments with fish have shown that uptake and accumulation take place directly from water and from food, and symptoms of toxicity have been observed (2)(3)(4)(5)(6). Determination of small amounts of CP is particularly difficult.…”
Section: Central Institute For Industrial Research (Ciir) Po Box 3mentioning
confidence: 99%